2022
DOI: 10.1017/s1047951122003365
|View full text |Cite
|
Sign up to set email alerts
|

A novel algorithm for classification of interatrial communications within the oval fossa in the newborn

Abstract: Background: An interatrial communication is present in most neonates. The majority are considered the “normal” patency of the oval foramen, while a minority are abnormal atrial septal defects. Differentiation between the two with transthoracic echocardiography may be challenging, and no generally accepted method of classification is presently available. We aimed to develop and determine the reliability of a new classification of interatrial communications in newborns. Methods and Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Interatrial communication is present in most neonates, mostly due to patent foramen ovale and in a minority due to a true atrial septal defect of “the ostium secundum” type [ 10 ]. As case number one had an exclusive left-to-right shunt, it could not be responsible for low oxygen saturation.…”
Section: Discussionmentioning
confidence: 99%
“…Interatrial communication is present in most neonates, mostly due to patent foramen ovale and in a minority due to a true atrial septal defect of “the ostium secundum” type [ 10 ]. As case number one had an exclusive left-to-right shunt, it could not be responsible for low oxygen saturation.…”
Section: Discussionmentioning
confidence: 99%
“…Details about the cohort profile for the Copenhagen Baby Heart Study and data obtained in the study are described in a previous publication [ 17 ]. We included neonates from CBHS where the TTE included visualization of the atrial septum in 2D with and without color Doppler and with adequate image quality to determine the presence or absence of an ASD [ 18 ]. We excluded neonates with concomitant major cardiac malformations, neonates with syndromes, and neonates where no ECG was obtained or where the cardiac examination (TTE and ECG) was performed more than 30 days after birth.…”
Section: Methodsmentioning
confidence: 99%
“…Echocardiograms were stored and analyzed using EchoPAC software (GE Healthcare, Horten, Norway). Echocardiograms were individually and systematically assessed for secundum-type ASDs by physicians trained in pediatric echocardiography using a novel algorithm for the assessment of interatrial communications in the oval fossa that was developed and validated in the CBHS and has been described in detail previously [ 18 ]. Analyses were based on several echocardiographic criteria, where we defined neonates as having an ASD in cases where color Doppler flow was crossing the atrial septum and 2D cross-sectional images showed either multiple visible communications (fenestrated ASD) or one single visible communication with either a diameter of ≥ 4 mm or a location in the inferior part of the atrial septum.…”
Section: Methodsmentioning
confidence: 99%